Exploring new battery knowledge by advanced characterizing technologies. Issue 3 (28th December 2021) - Wang, Liguang; Liu, Tiefeng; Wu, Tianpin; Lu, Jun
Abstract: Exploration of science and technologies represents human's thirst for new knowledge and new life. Presently, we are in a stage of transferring the use of fossil fuels to renewable energy, which urgently calls for new energy materials and techniques beyond the boundary of human knowledge. On the way of scrutinizing these materials and surmounting the bottleneck of their performances, characterizing technologies are of critical importance in enabling the revealing of materials regarding their structural and chemical information, eventually establishing the correlations between microstructures and properties at the multiscale levels. Regrettably, traditional characterizations are hard to simultaneously probe electrochemistry with these chemical and physical structural evolutions, especially under operando conditions, or offer high‐resolution images of materials sensitive to electron‐beam irradiation. To this end, various advanced characterizing and diagnosing technologies recently developed, such as transmission X‐ray microscopy and cryo‐transmission electron microscopy, have demonstrated their benefits in understanding the energy storage behaviors of high‐performance energy materials (such as layered transition oxide cathode and Li metal anode). Benefited from new knowledge, the progress of high‐capacity electroactive materials is significantly accelerated. Here, we timely review the breakthroughs in emerging techniques and discuss how they guide the design of future battery materials to achieve the ultimate carbon neutrality. Abstract : Advanced characterizing technologies are of critical importance in enabling the revealing of materials regarding their structural and chemical information, eventually establishing the correlations between microstructures and properties at the multiscale levels.